Web-Based Batik Clothing Information System on Cv. Desta Bogor - Nanang Nuryadi; Nuryanti Nuryanti (Journal of Applied Engineering and Technological Science (JAETS), 2022)
CV.Desta is one store that is located in the Bogor area. On the CV.Desta authors conducted an analysis of sales system that is running thr current. Sales are only made in the store are still not getting the maximum result. Income and lact of promotion does not necessarily make CV.Desta still not known to the public. Moreover want development and expansion of sales and increased sales not only in the store. To overcome such problems, the authors intend to try to handle the sales process by designing an information system is a web-based sales of goods or more often in the know as e-commerce using the programming language php and mysql